Mistaken Diabetic Ulcers: A Case of Bilateral Foot Verrucous Carcinoma - Vanessa Di Palma; Jill P. Stone; Andrew Schell; Jeffrey C. Dawes (Hindawi Limited, 2018)
Verrucous carcinoma (VC) is a rare, low-grade, and well-differentiated variant of squamous cell carcinoma. These tumors are slow-growing and exophytic and have a negligible incidence of metastasis. Treatment is complete surgical resection, ideally by Mohs micrographic surgery, to ensure adequate clear margins. Cutaneous VC predominantly occurs on the plantar surface of the foot and rarely occurs in multiple sites. This case study describes the fourth reported occurrence of bilateral VC of the feet in a woman with chronic diabetic foot ulcers. The case provides further support for persistent wounds contributing to the development of this lesion and describes their role in the characteristic delay in diagnosis of VC.